Responses of the soil microbial community to nitrogen fertilizer regimes and historical exposure to extreme weather events: Flooding or prolonged-drought. (March 2018) - Nguyen, Linh T.T.; Osanai, Yui; Lai, Kaitao; Anderson, Ian C.; Bange, Michael P.; Tissue, David T.; Singh, Brajesh K.
Abstract: Extreme weather events, including flooding and prolonged-drought, may establish long-lasting effects on soil biotic and abiotic properties, thus influencing ecosystem functions including primary productivity in subsequent years. Nitrogen (N) fertilizer addition often improves soil fertility, thereby potentially alleviating legacy effects on soil function and plant productivity. The soil microbial community plays a central role in mediating soil functioning; however, little is known about the legacy impacts of extreme weather events and N fertilizer addition on soil bacterial communities and the key processes involved in carbon (C) cycling. Here, the potential legacy effects of waterlogging, prolonged-drought and N fertilizer addition (0, 100, 200 and 300 kg N/ha) on soil bacteria and microbial respiration were investigated. The abundance, diversity and composition of the bacterial community, and basal and induced-respiration rates, in a farming soil system were examined, using quantitative PCR, high-throughput DNA sequencing, and MicroResp™. Soils previously exposed to short-term waterlogging events and prolonged-drought (by air-drying for 4 months) were used in our study. Prolonged drought, but not waterlogging, had a strong legacy effect on the soil bacterial community and microbial respiration. The addition of N fertilizer up to 300 kg N/ha could not fully counteract the legacy effects of prolonged-drought on soil bacteria. However, N addition did increase bacterial abundance and diversity, and inhibited soil microbial respiration. Significant correlations between microbial respiration and bacterial community structure were observed, but N addition weakened these relationships. Our results suggest that the resilience (rate of recovery) of soil bacterial communities and functions to prolonged-drought is limited in farming systems, and therefore, may take a long time to recover completely. Subsequently, this should be explicitly considered when developing adaptation strategies to alleviate the impacts of extreme weather events. Highlights: Extreme weather events induce legacy impact on soil microbial communities and activities. Prolonged droughts have stronger legacy impact than waterlogging treatment on microbial communities. Nitrogen addition mitigates but not completely counteracts legacy impacts of extreme weather events. Correlation between microbial community and soil respiration is weakened by N addition.